The Role of Contemporary Interactive Art Works Economically and Culturally "An Analytical Study" (Al-Academy, 2021)
The aim of the research is to identify the economic and cultural role of contemporary interactive artworks from the public's point of view, with knowledge of the most important obstacles and proposals to improve the level of design and spread of interactive artworks. The descriptive approach was used, and the researcher used a questionnaire tool that was distributed to the audience for the events of Noor Al Riyadh (2021) and the size of the participating sample was (194) individuals from all spectrums of society. It was found through the results of the existence of public approval of the economic role of contemporary interactive artworks, as they contribute to supporting the national economy. It attracts the public to attend various paid entertainment events, and the cultural role of contemporary interactive artworks in society is evident, in terms of providing a broad source for the development (innovation and artistic taste) of the audience, as it turns out that the most important obstacles to the design and spread of interactive artworks among the audience. It lies in the lack of sufficient advanced premises for interactive art galleries. In addition, the lack of financial and encouragement support by the responsible authorities for the artists. Moreover, the lack of organized training, and it was found that the most important proposals to improve the level of design and spread of interactive artwork among the public by the participants in Noor Al Riyadh activities focused on improving the levels of interactive artwork to be attractive to the public. In addition, seek to increase media interest in interactive arts models